2000
DOI: 10.1007/s002530000373
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the physiological and agricultural characteristics of peat-based Bradyrhizobium japonicum inoculants after long-term storage

Abstract: Commercial soybean inoculants processed with sterilised peat and stored at 20 degrees C for 1-8 years were used as experimental materials to assess the changes in the physiological activity of Bradyrhizobium japonicum after storage. Viable counts decreased and physiological characteristics of the bacterium changed during storage, with an increase in the time taken for colony appearance on a medium without yeast extract, an increase in the lag time for nodule appearance on soybean grown in glass tubes and a dec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(6 citation statements)
references
References 0 publications
1
5
0
Order By: Relevance
“…The correspondence of number of nodules with their weight in this work, especially in inoculated treatments, also confirms the findings of Lawson and Quainoo (2008) that nodule dry biomass followed the same pattern as the nodule count. Revellin et al (2000) also observed that higher numbers of nodules per plant resulted in higher plant biomass. The observation in this study of a significant high level of nodulation at full pod stage (a possible indication of increased N 2 fixation) contradicts the finding of Zapata et al (1987) that maximum N 2 fixation occurs between the flowering and early pod stages of soybean development.…”
Section: Discussionmentioning
confidence: 69%
“…The correspondence of number of nodules with their weight in this work, especially in inoculated treatments, also confirms the findings of Lawson and Quainoo (2008) that nodule dry biomass followed the same pattern as the nodule count. Revellin et al (2000) also observed that higher numbers of nodules per plant resulted in higher plant biomass. The observation in this study of a significant high level of nodulation at full pod stage (a possible indication of increased N 2 fixation) contradicts the finding of Zapata et al (1987) that maximum N 2 fixation occurs between the flowering and early pod stages of soybean development.…”
Section: Discussionmentioning
confidence: 69%
“…CMC and AE are the most common high molecular synthetic compounds for entrapped microbes [51, 52], can stick closely to coated materials, sustain live rhizobial cells, are harmless to cotyledons, and are not toxic in the environment [53, 54]. While many reports have focused on the ability of polymers to sustain rhizobia on legume seeds, especially on cowpea and soybean seeds [49, 5558], their effects on root nodulation and N-fixation have not been well quantified. CMC is a cellulose-derived ester and pre-studies indicated that CMC has proper chemistry characteristics for stable microbe storage [48, 59, 60].…”
Section: Discussionmentioning
confidence: 99%
“…Hume and Blair (1992) found a higher number of Bradyrhizobium viable cells, when using these types of inoculants in soils with low nitrate content in sites where grain yield approached 3.2 Mg ha −1 . Revellin et al (2000) subsequently demonstrated a higher number of nodules per plant and a larger response to inoculation with liquid inoculants in experiments where grain yield approached 4.7 Mg ha −1 , though this response was attained via comparison of inoculated versus uninoculated treatments on a field that had no previous soybean cropping history. Other sets of experiments in tropical soils without soybean history showed increases in N 2 fixation and nodule number when using sterile-peat or liquid inoculants , Thao et al, 2002 but these responses were observed at sites where the grain yields were no greater than 2.5 Mg ha −1 .…”
Section: Inoculation and Grain Yield Potentialmentioning
confidence: 99%